2022
DOI: 10.30574/msarr.2022.6.2.0079
|View full text |Cite
|
Sign up to set email alerts
|

Gas gangrene in pregnancy, delivery and abortions requiring urological and surgical management; our experiences in Port Harcourt, Nigeria

Abstract: Introduction: In spite of a high contribution of 26.7% to 35.0% of sepsis to maternal mortality in our hospital, there is little or no documentation about pyogaseous infections in pregnancy in the area. We present here a series of cases of different forms and presentations of pyogaseous infections managed at designated hospitals in Port Harcourt and its environs. Materials and Methods: Using a common proforma containing clinical and relevant laboratory tests, consecutive patients that presented to designated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Clostridium infections and myonecrosis may also spread centripetally from a peripheral maternal extra-uterine source to the maternal uterus and the fetal tissues. An example of the centripetal spread of clostridia infection and advancing myonecrosis was described by Sapira MK et al [43]. In that report, in a mother aged 35 years at mid-trimester of gestation, the infection spread from the maternal right hypochondrium toward the pelvis.…”
Section: Stages Of Spread Of Clostridia Infectionsmentioning
confidence: 91%
“…Clostridium infections and myonecrosis may also spread centripetally from a peripheral maternal extra-uterine source to the maternal uterus and the fetal tissues. An example of the centripetal spread of clostridia infection and advancing myonecrosis was described by Sapira MK et al [43]. In that report, in a mother aged 35 years at mid-trimester of gestation, the infection spread from the maternal right hypochondrium toward the pelvis.…”
Section: Stages Of Spread Of Clostridia Infectionsmentioning
confidence: 91%
“…Our previous studies on gas gangrene in pregnancy and its outcome, and information in the literature indicated that the disease could arise from infections originating from fetal tissues, or any part of the maternal extra genital or genital tissue sites [1,2]. There has also been the notion that the disease occurs mostly in low-income countries with limited resources, and that its early features are non-specific.…”
Section: Introductionmentioning
confidence: 99%